Study For Water Shutoff Using Tandem Through Tubing Bridge Plugs Technique, Case Study - et. al., Dr. Ahmed Samer Azab, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Increasing water production rate is from one of the well knownmain problems that face any oil producer in the world. Although this problem is most happen in old wells, this can also happen in new drilled wells as well. It causes differenteconomic problems for oil produced companies. First, increasing water production affectsproduced wells performance and reduced their production lifetime. The high percentage of the water in the wellbore increasing the hydrostatic pressure (weight of the fluid column) which cause increasing in the lifting power required. which increasingoil and gas production cost per barrel and causing toreduce the drawdown. As an example, if the well is gas lift well, the quantity of gas needs to be injected for lifting the fluid from the wellbore to the surface is increasing with the production of heigh water cut than without producing water. Increasing water cut percentage and Water production also increases the possibility of corrosion, scale and has negative effect on the field equipment starting from the wellbore itself to the surface facilities. Also another serious and important problem is increasing produced water separating cost, treatment, and disposal is a great challenge to oil producers budgets. It costs almost $1.1 billion/year in averageforseparation and disposal of the produced water. Found solution for that type of production help in minimizingcost for the operators and increasing the yearly profit of their operations. Then, water shutoff jobs and operations are very essential. Finally, bythe good understandingfor the formation characterizations and otherfield problems of the field, we can avoid un-necessary water production during the wellbore designing stage.Through tubing bridge plugs (TTBPs) as one of water shut-off (WSO) workovers in the Belayim Fields resulted in average gradualproduction increasing of 2450 bopd.The Average water cut percentage (WC) reduced from 54% to 15%. 87WSOworkoversjobs done since December 1991. Technical evaluation and economical income successful evaluation approaches 90%. Just below 4.5 million dollars companies spent for an average cost of 60,500 dollars per job. Costs spent in less than two days equal to using income from a13 dollars per barrel from crude oil price. Depend on achieved results during the last 4.5 years, these WSO (water shut off)workoversdone in Belyim Field as an effective and on-going cases history for running and set zone water production control. Water production probleminBelayim Field gradually increasing during the last 10 years.Which result indropping inoil production rates.Depend on the reservoir characteristics; lower water zone isolated using through tubing bridge plugs (TTBPs)usingSchlumberegerelectric line units. Dump bailer tools used to put a 14 feet cement cap above the TTBPs to have means of a permanent pressure seal. After 24-hourswaiting on cement time, wells returned back to production with a great change and higher oil rate and very good reduction in Water Cut. Rigless cost for TTBP water shut off workover becomes much less than conventional rig water shut offoperations which result in averaged more than 450,000 dollars per job. Before December 1990,conventional rig operationsWSOwasonly the method used in Belayim Field. now, riglessWSOworkovers becomesa very important for reducing cost or to control cost with financial language.Rigless WSOoperations becomes alsovery important reservoir control tool forincreasing oil production and reducing water production which helps to save reservoir energy.